2011
DOI: 10.1016/j.febslet.2011.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of miR-23b may contribute to activation of the TGF-β1/Smad3 signalling pathway during the termination stage of liver regeneration

Abstract: Edited by Veli-Pekka LehtoKeywords: MicroRNAs miR-23b Liver regeneration Transforming growth factor-b1 Smad3 a b s t r a c t MicroRNAs (miRNAs) are known to play important roles in liver regeneration, although the role of miRNAs associated with the termination of liver regeneration is not as well studied. Here we reported the down-regulation of miR-23b in the termination stage of liver regeneration in rats. In addition, Smad3 was identified as a target of miR-23b during liver regeneration. Up-regulation of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 28 publications
4
56
0
Order By: Relevance
“…First, certain similar miRNA changes are shared after hepatitis B (HBV) or salmonella infection and in our model. As reported, miR-27b-5p 56 and miR-23b-3p 57,58 were upregulated after HBV infection, and miR-26b, 59 mir-532-5p, 60 and mir-27b 60 were upregulated after salmonella infection. These miRNAs show the same tendency of changes after Ab stimulation.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…First, certain similar miRNA changes are shared after hepatitis B (HBV) or salmonella infection and in our model. As reported, miR-27b-5p 56 and miR-23b-3p 57,58 were upregulated after HBV infection, and miR-26b, 59 mir-532-5p, 60 and mir-27b 60 were upregulated after salmonella infection. These miRNAs show the same tendency of changes after Ab stimulation.…”
Section: Discussionmentioning
confidence: 52%
“…These viral proteins can trigger cancer-related genes and motivate several signaling pathways including genetic instability, inflammatory, and host immune responses. 56 These pathways, especially the proliferation 57,61-63 and apoptosis 58,63 pathways, were included in our model. Thirdly, as we made predictions with limited confirmed miRNA data, some possible pathways might be missing as an inevitable undesired result.…”
Section: Discussionmentioning
confidence: 99%
“…8 It has been shown that certain micro RNAs may be involved in the termination of liver regeneration. 9,10 In addition, the ablation of integrin-linked kinase leads to enhanced liver proliferation.…”
Section: Partial Hepatectomy As a Model For The Study Of Mechanisms Wmentioning
confidence: 99%
“…When injured or undergoing a partial hepatectomy (PH), hepatocytes are rapidly activated, proliferate, and restore the lost liver tissues; these processes are called liver regeneration (LR) (Taub, 2004;Xu et al, 2004). In recent years, an increasing number of studies have shown that microRNAs (miRNAs) such as miR-127, miR-34a, and miR-23b, play an important role in liver growth, development, and regeneration (Chen et al, 2011;Yuan et al, 2011;Pan et al, 2012). miRNAs are a class of endogenous, small regulatory RNA molecules with a length of about 25 nucleotides (nt), and are found mostly in introns and intergenic regions.…”
Section: Introductionmentioning
confidence: 99%